Integrating Education into Product Diversification: A Value Chain Analysis of Brick and Wall Shops - Ahdi Ahdi; Nandang Nandang; Dela Aprilia Fauziah; Siti Maritza Nurfauziyyah; Azizah Fauziyah (International Journal Corner of Educational Research, 2025)
ndonesia's economic development from the early 1980s to the mid-1990s showed a positive trend, with average growth reaching approximately 6.4% per year. However, periods of economic instability have also contributed to trade deficits, creating additional challenges for business sustainability. In such conditions, business diversification becomes an important strategy to strengthen competitiveness. Diversification can be considered successful if it increases revenue, expands market share, and creates synergy among various business lines, enabling companies to survive and compete more effectively in an increasingly competitive industry. The Brick and Lost Wall Shop in Bekasi, West Java, is a business that focuses on providing decorative building materials, particularly brick and loster wall products. Toko Bata Tempel and Loster has also followed technological developments by utilizing digital platforms to promote its products. One of the platforms used is Google Maps, where the shop is registered not only as a business location but also as a source of detailed information about products, services, and customer reviews. Currently, the shop still concentrates on brick and loster products. However, to enhance competitiveness and respond to increasingly diverse consumer demands, it is necessary to consider product diversification strategies. From an educational perspective, diversification efforts can also be supported through knowledge transfer, training, and managerial learning related to value chain analysis, digital marketing, and innovation. Integrating educational elements into business development will help business owners improve strategic decision-making, optimize resources, and strengthen long-term sustainability.